IMPACT SYNDROME PREVENTION IN THE CLASSROOM (Fiep Bulletin - online, 2012)
This study was conducted with 40 teachers from Santa Terezinha de Itaipu, Parana, Brazil with more than 15 years of professional work. The musculoskeletal disorders in the joints resulting from their activities were collected through the use of a checklist adapted from Couto, (2007). The perception of pain, however, was performed through the use of a scale ranging from 0 to 10 points, according to the Borg, (2000) subjective perception of pain. It could be concluded that the activities performed by the teacher on the blackboard provide significant deterioration of the joints, especially on the shoulder joints.
Keywords: Teachers; Shoulder; Classroom